Lumio Learning Media by Smart in the Subject of Faith and Morals on Student Learning Outcomes - Rochmat, Cecep Sobar; Ajitata, Annisa (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Aqidah and Akhlak (Faith and Morals) are two important subjects that aim to build students' character through faith and positive behavioral habits. However, the implementation of these subjects faces various challenges, including a conventional learning process and the use of limited media. So that it can affect students' interest and motivation in learning as well as student learning outcomes. This media aims to determine the effect of Lumio 's Smart Learning Media about Aqidah and Akhlak on student learning outcomes. The method used in this study was a quantitative experiment with a true experimental design that used pretest-posttest. The subjects of this study were students of State Junior High School 5 Sragen. Data collection techniques were obtained based on the results of interviews, observations, tests, and documentation conducted by researchers. Data analysis used descriptive statistics, including normality tests, homogeneity tests, and independent sample t-tests with SPSS 27. The results showed that the significance value of Sig. (2-tailed) was 0.019 < 0.05, so Ho was rejected and Ha was accepted. Based on the data above, it can be interpreted that the significance value of Sig. (2-tailed) was 0.019 < 0.05, so Ho was rejected and Ha was accepted. Thus, it can be concluded that there is a significant influence on student learning outcomes in the control and experimental classes. This means that the use of Lumio by Smart Learning Media in the subject of faith and morals has a significant influence on improving student learning outcomes compared to conventional learning.